Concept of Blockchain Technology (International Journal of Innovative Computing, 2019)
Blockchain, Bitcoin's core technology, and spinal cord have received enthusiastic attention since the last couple of decades. The Blockchain serves as a paradigm for distributed and unchangeable computations for bitcoins and cryptocurrencies. The key features behind this technology are to create a reliable, secure, transparent, decentralized, and reliable autonomous ecosystem. It is useful for a variety of applications, especially for legacy devices, resources, and infrastructure. In this article, we presented a technical overview, its application, and the challenges associated with blockchain technology and cryptocurrencies. This study aims to provide a ground-breaking overview and future research direction and promising importance of Blockchain.
Keywords: internet of things; bitcoin; digital signature; classification